"How would you answer if a client asked if you'd been raped?": Towards a political critique of psychotherapy placements. (4th January 2018) - Lee, Deborah A.
Abstract: This paper takes an intrusive, unacceptable clinical placement interview question as a starting point for a political critique of psychotherapy placements.